Men to devils, devils to men: Japanese war crimes and Chinese justice - Kushner, Barak (Harvard University Press, 2015)
Defeat in denial : the regional impact of Japan's surrender -- Devil in the details : Chinese policies on Japan's war crimes -- Flexible imperial identity : administering postwar legal guilt -- Chinese nationalist justice : the KMT trials -- Taiwan : political expediency and Japanese imperial assistance -- An unsatisfying peace : shifting attitudes on war crimes -- Socialist magnanimity : the CCP trials